Exploring Academic Writing Proficiency of Tertiary EFL Learners of Bangladesh: A Pedagogical Implication - Patwary, Md. Nurullah; Reza, Md. Mohoshin; Akhter, Humayra; Chowdhury, Swarna (Integrated Journal for Research in Arts and Humanities, 2023)
It is essential that tertiary EFL students become proficient in all key aspects of writing, such as content, arrangement of ideas, usage of appropriate vocabulary, use of language and grammatical precision, and mechanics, in order to improve their formal writing skills. As a result, the current study's objective is to assess the level of writing competency of tertiary EFL students in terms of the key writing components and to provide some recommendations for EFL teachers, syllabus writers, and material designers. This study is qualitative in nature that collected 49 narrative essays from 49 tertiary students. The participants comprised both English and non-English majors from seven private and public universities in Bangladesh. The data were generated from English writing tests where students wrote one narrative essay. The texts were then analyzed on the basis of the analytic writing rubrics proposed by Jacobs et al. (1981) to see students’ writing ability in general. The findings of the analysis indicate that Bangladeshi tertiary EFL learners’ proficiency in all the major components falls in the category of Fair to Poor. The findings also indicate that the most challenging writing skills for the learners are the use of language and the use of vocabulary. The study concludes with some pedagogical suggestions for tertiary EFL teachers, syllabus designers, and material designers. This study stands out as unique and important since little research has previously attempted to evaluate the writing proficiency levels of Bangladeshi tertiary students under the key writing components.